The Economic Impact of CPO (Crude Palm Oil) Industry Development on the Lives of Fishermen Communities in Lubuk Gaung Village, Dumai City - Octavianti, Mila; Warningsih, Trisla; Nugroho, Firman (Faculty of Fisheries and Marine, Universitas Riau, 2024)
As much as 90% of the fisheries industry in Dumai City comes from capture fisheries. The capture fisheries industry is a crucial industry that requires more attention from the government because of its enormous potential. Every year, there is a decrease in the number of fishing households in Dumai City. The reason is the uncertainty of income received and the existence of other business sectors. Fishing communities depend on fisheries resources for their livelihoods. However, the fishing profession in Dumai City is susceptible to changes around it, including changes due to the development of the CPO industry. This study was conducted to analyze the economic impact of the CPO Industry's development on the Lubuk Gaung Village fishing community. This research uses a quantitative survey method, followed by quantitative descriptive data analysis and hypothesis testing with a paired sample t-test. The fishing community in Lubuk Gaung Village felt the economic impact of various indicators. Total household income experienced a significant increase of IDR 2,452,880. Total household expenditure also experienced a significant increase, amounting to IDR 1,185,800. Meanwhile, in terms of asset ownership, fishermen have experienced an increase in asset ownership to meet their daily needs since the existence of the CPO IndustryThe Economic Impact of CPO (Crude Palm Oil) Industry Development on the Lives of Fishermen Communities in Lubuk Gaung Village, Dumai City